Produksi dan Kontribusi Ruang Informal pada Jalanan Gang Ampiun - Muzaki, Azzam; Ramadani, Nazwa Novita; Novalia, Arfatuz Zahra; Shidqi, Ihsan; Yesekal, Muhamad Haikal; Siregar, Hasim Shakti (Jurnal Arsitektur Wastu Padma, 2024)
This study aims to examine the phenomenon of the production and reproduction of public spaces, specifically streets, in Gang Ampiun, Jakarta. Referring to Henri Lefebvre's theory of space production as a result of social processes, various social factors play a significant role in shaping these spaces. From an architectural perspective, the dynamics of this process are intriguing for understanding the true formation of space. In architectural studies, students and architects often rely on standards and references, whereas actual users create and modify spaces according to their own needs. This research employs a qualitative rationalistic approach based on Lefebvre’s concept of space production. The findings reveal that the social and environmental processes in Gang Ampiun contribute to the formation of informal spaces that fulfill community needs. These informal spaces play a crucial role in maintaining the area's social life. The community, as users, reproduces these spaces through power dynamics and mutual agreements among them.